The Effect of The CTL Approach on Student’s Creative Thinking Skills and Mathematics Learning Outcomes - Herkun Santoso; Sunardi Sunardi; Tri Dyah Prastiti (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2023)
The research aims to analyze the effect of the Contextual Teaching and Learning (CTL) approach on creative thinking skills and learning outcomes and to describe the implementation of mathematics learning using the Contextual Teaching and Learning approach for class VI students at SDN 2 Ketapang Banyuwangi on the material Circumference and Area of a Circle. A mixed method was used in this research. The population in this research were all of the sixth-grade students for the 2021/2022 academic year, with a total of 54 students. The samples in this research were 23 students in the control class and 23 students in the experimental class, respectively, where the sampling technique used the Yamane formula. Statistical analysis used comparative analysis (t-test) and the N-gain test. The results showed: 1) the post-test t-test results between the control and experimental classes with a t-value of 4.791 (p-value = 0.000) and the t-test results differed between the post-test and pre-test scores between the control and experimental classes with the t-count value of 5.368 (p-value = 0.000). Both p-values are less than α (0.05), which means that the CTL approach influences students' creative thinking skills. 2) the post-test t-test results between the control and experimental classes with a t-count value of 2.136 (p-value = 0.038), the t-test results are the difference between the post-test and pre-test values between the control and experimental classes with a t-count value of 3.038 (p-value = 0.004). Both p-values are less than α (0.05), which means that the CTL approach has an effect on students Mathematics learning outcomes. Thus, the CTL approach has an effect on creative thinking skills and the mathematics learning outcomes of grade VI students on the circumference and area of a circle.